Diabetes and Sarcopenic Obesity: Pathogenesis, Diagnosis, and Treatments - Wang, Mina; Tan, Yan; Shi, Yifan; Wang, Xu; Liao, Zehuan; Wei, Peng (Frontiers in Endocrinology, 2020)
Sarcopenic obesity and diabetes are two increasing health problems worldwide, which both share many common risk factors, such as aging and general obesity. The pathogenesis of sarcopenic obesity includes aging, physical inactivity, malnutrition, low-grade inflammation, insulin resistance, and hormonal changes. Nevertheless, there are two major forms to cause diabetes: impaired insulin secretion and impaired insulin action. Furthermore, the individual diagnosis of obesity and sarcopenia should be combined to adequately define sarcopenic obesity. Also, the diagnosis of diabetes includes fasting plasma glucose test (FPG), two-hour oral glucose tolerance test (OGTT), glycated hemoglobin (A1C), and random plasma glucose coupled with symptoms. Healthy diet and physical activity are beneficial to both sarcopenic obesity and diabetes, but there are only recommended drugs for diabetes. This review consolidates and discusses the latest research in pathogenesis, diagnosis, and treatments of diabetes and sarcopenic obesity.